2013
DOI: 10.1186/1471-2407-13-351
|View full text |Cite
|
Sign up to set email alerts
|

SISH/CISH or qPCR as alternative techniques to FISH for determination of HER2 amplification status on breast tumors core needle biopsies: a multicenter experience based on 840 cases

Abstract: BackgroundUntil now, FISH has been the gold standard technique to identify HER2 amplification status in ambiguous cases of breast cancer. Alternative techniques have been developed to increase the capacities of investigating HER2 amplification status. The aims of this multicenter study in a large series of breast cancer patients were to prospectively compare the level of performance of CISH, SISH, and qPCR alternative techniques on paraffin-embedded core biopsies with “gold standard FISH” for evaluation of HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 43 publications
(50 reference statements)
3
34
1
Order By: Relevance
“…We first optimized our rqPCR assay for HER2 CNs relative to reference gene CNs in GC. We initially chose three candidate genes, RPPH1 (14q11.2), TAOK1 (17q11.2) and EFTUD2 (17q21.31), on the basis of previous reports [11,[20][21][22]] to avoid false increases or decreases in HER2 CN ratios owing to their normal CN variations as well as frequent CN alterations in GC. In microarray-based CN data obtained from the publically available CCLE database using bioinformatics, the smallest variation was found for RPPH1 among these three candidates in 20 GC cell lines (2.107 ± 0.4045, 2.023 ± 0.4694 and 2.207 ± 0.4617 for RPPH1, TAOK1 and EFTUD2, respectively; mean ± SD; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…We first optimized our rqPCR assay for HER2 CNs relative to reference gene CNs in GC. We initially chose three candidate genes, RPPH1 (14q11.2), TAOK1 (17q11.2) and EFTUD2 (17q21.31), on the basis of previous reports [11,[20][21][22]] to avoid false increases or decreases in HER2 CN ratios owing to their normal CN variations as well as frequent CN alterations in GC. In microarray-based CN data obtained from the publically available CCLE database using bioinformatics, the smallest variation was found for RPPH1 among these three candidates in 20 GC cell lines (2.107 ± 0.4045, 2.023 ± 0.4694 and 2.207 ± 0.4617 for RPPH1, TAOK1 and EFTUD2, respectively; mean ± SD; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…[9] IHC is a preferred method for screening and determining cases which need to be genetically evaluated, [11] and IHC using scoring tools such as the "Hercept scale" and, more recently, the ASCO/CAP scale, was the simplest way to identify positive cases likely to benefit from trastuzumab that is susceptible to interobserver variability and, as with any assay technique, required standardization and validation. [12] Thin tissue section FISH is the routinely used method for the detection of gene status in paraffin-embedded breast cancer samples. [13] However, according to this scale, HER2 amplification of 2+ cases had to be confirmed by FISH [12].…”
Section: Introductionmentioning
confidence: 99%
“…[12] Thin tissue section FISH is the routinely used method for the detection of gene status in paraffin-embedded breast cancer samples. [13] However, according to this scale, HER2 amplification of 2+ cases had to be confirmed by FISH [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors observed 95% compatibility between FISH and quantitative PCR (qPCR) results carried out in DNA isolated from paraffinembedded tissue samples. The outcomes are more promising than the results of analyses performed by RT-PCR that RNA is more sensitive to degradation during the paraffining process [29].…”
Section: The Significance Of Her2 Status In Breast Cancer Patients Qumentioning
confidence: 99%
“…Gullo et al had observed that HER2 gene amplification is higher in primary tumors rather than in metastases. Moreover, the presence of HER2 abnormalities is associated with the shortening of OS and has no effect on the advancement of disease at the time of diagnosis, advancement of tumor differentiation and expression of estrogen and progesterone receptors [29,30].…”
Section: The Significance Of Her2 Status In Breast Cancer Patients Qumentioning
confidence: 99%